Gesture controlled robotic arm - Cheah, Kah Hou (2018)
Robotic arm is widely used in various fields such as industry, medical and even military due to its abilities of high accuracy, efficiency and repeatability. Some special application in military such as bomb disposing by bomb disposal robot, human control is needed for the robotic arm on top of it. However, the bomb disposal robot typically controlled by special design joystick or gaming console such as Playstation controller, the control of those controller for the robotic arm is complicated and unintuitive. Thus, the goal of this project is to build a 6-axis robotic arm and implement gesture control into it. Leap motion sensor technology is part of the study since the sensor was used for capturing the gestures as the control of the robotic arm. The captured gesture data was then extracted and processed in the Processing software and sent to Linkit board by serial communication, the Linkit board was responsible to disassemble the data to drive the servo motors. The 6-axis robotic arm was built and gesture control with the Leap motion sensor was successfully implemented into it as the results.